2015
DOI: 10.1007/s12010-015-1682-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression Analysis of Phenylalanine Ammonia Lyase Gene and Rosmarinic Acid Production in Salvia officinalis and Salvia virgata Shoots Under Salicylic Acid Elicitation

Abstract: Partial fragments of phenylalanine ammonia lyase (PAL) genes were cloned and characterized from Salvia officinalis (SoPAL) and Salvia virgata (SvPAL). Different concentrations (250 and 500 μM) of exogenous salicylic acid (SA) were used when correlation between PAL expression and rosmarinic acid (RA) accumulation was compared. The results showed that the deduced cDNA sequences of the partial genes had high similarities with those of known PAL gene from other plant species. Semi-quantitative reverse transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 31 publications
(48 reference statements)
2
11
0
Order By: Relevance
“…Here, we reported that ABA induced the accumulation of RA and phenolic compounds. Our findings are consistent with those of the previous studies on other plant species which reported that the content of RA and phenolic compounds was increased by application of biotic and abiotic elicitor (Yan et al 2006, Bauer et al 2009, Kim et al 2013, Ejtahed et al 2015. In this study, ABA was used as an elicitor to examine the relationship between the expression of rate-limiting enzymes in the two RA biosynthesis pathways and accumulation of RA in the shoot cultures.…”
Section: Discussionsupporting
confidence: 92%
“…Here, we reported that ABA induced the accumulation of RA and phenolic compounds. Our findings are consistent with those of the previous studies on other plant species which reported that the content of RA and phenolic compounds was increased by application of biotic and abiotic elicitor (Yan et al 2006, Bauer et al 2009, Kim et al 2013, Ejtahed et al 2015. In this study, ABA was used as an elicitor to examine the relationship between the expression of rate-limiting enzymes in the two RA biosynthesis pathways and accumulation of RA in the shoot cultures.…”
Section: Discussionsupporting
confidence: 92%
“…This regulation consequently resulted in the increase of RAS activity observed starting from the end of O 3 treatment, as well as of RA content at 24 h FBE. As reported by Ejtahed et al [46], no positive relation was observed between the expression intensity of PAL and the accumulation of RA, indicating that PAL is not the rate-determining step in RA biosynthesis and other unknown factors might participate in RA synthesis. It is worth noting that PAL genes have been cloned from different plant species where they usually exist in polygenic families, with three to nine members [47,48].…”
Section: Discussionmentioning
confidence: 57%
“…The results of the present study are in agreement with the latter. Phenylalanine ammonium lyase (PAL), as the first committed enzyme in the phenylpropanoid metabolism, plays a key role in the biosynthesis of phenolic compounds in herbs (Ejtahed et al, 2015 ). Saba et al.…”
Section: Resultsmentioning
confidence: 99%
“…The results demonstrated that total phenolic and total flavonoid in the biosynthesis of phenolic compounds in herbs (Ejtahed et al, 2015). Saba et al (2012) indicated a significant positive correlation between content of polyphenols and activity of PAL enzyme.…”
Section: Total Phenolic Content (Tpc) and Total Flavonoid Content (Tfc)mentioning
confidence: 87%